The use of hydrotherapy in women during labour - Urbano Bernal, Elena María; García González, Jessica (Enfermería Cuidándote, 2025)
Introduction: Obstetric care has undergone a great evolution over many years. Therefore, as more women seek more natural and less invasive birth options, hydrotherapy is presented as a valuable alternative, promoting a more comfortable and empowering environment during one of the most significant moments of life.Methods: A narrative bibliographic review was carried out using several databases including PubMed, Cochrane, Scielo and Web of Science. Likewise, articles were obtained through a reverse search. The search strategy was carried out by combining the descriptors “pregnancy”, “hydrotherapy”, “effects” and “effect pain”.Results: In the search, 18 articles that met the inclusion criteria were selected. The results obtained indicate that hydrotherapy provides positive sensations allowing relaxation and good pain management. In addition, it provides postural changes and the woman's ability to control during childbirth.  However, side effects include the risk of umbilical cord avulsión, as well as an increased risk of uterine infection without hospitalization.Discussion: These findings suggest that the use of hydrotherapy is an alternative non-pharmacological analgesic method for childbirth due to the comfort provided, the ability to control and the early skin-to-skin contact among others. It is recommended that the pregnant woman has enough information about this alternative to determine for herself whether to use it.
Keywords: Birth; Hidrotherapy; Newborn; Pain; Pregnant; Water